2020
DOI: 10.3390/metabo10030082
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dried Blood Spot-Based Metabolomics: A Targeted, Broad-Spectrum, Single-Injection Method

Abstract: Dried blood spots (DBS) have proven to be a powerful sampling and storage method for newborn screening and many other applications. However, DBS methods have not yet been optimized for broad-spectrum targeted metabolomic analysis. In this study, we developed a robust, DBS-based, broad-spectrum, targeted metabolomic method that was able to measure over 400 metabolites from a 6.3 mm punch from standard Whatman 903TM filter paper cards. The effects of blood spot volumes, hematocrit, vacutainer chemistry, extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 40 publications
(51 reference statements)
3
39
2
Order By: Relevance
“…Differentiating SCLC from NSCLC (large cell carcinoma or basaloid squamous cell carcinoma) using noninvasive methods is essential since the therapeutic strategies and clinical prognoses are significantly different. Several noninvasive blood metabolomic and dynamic multiphase computed tomography (CT) methods have been recently developed to discriminate SCLC and NSCLC [27][28][29][30]. However, blood metabolomic biomarker results that showed the differentiation of SCLC and NSCLC tumor types has not been confirmed with large cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating SCLC from NSCLC (large cell carcinoma or basaloid squamous cell carcinoma) using noninvasive methods is essential since the therapeutic strategies and clinical prognoses are significantly different. Several noninvasive blood metabolomic and dynamic multiphase computed tomography (CT) methods have been recently developed to discriminate SCLC and NSCLC [27][28][29][30]. However, blood metabolomic biomarker results that showed the differentiation of SCLC and NSCLC tumor types has not been confirmed with large cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…As first lockdown in Italy began at the end of February 2020 and finished at the end of May 2020, study periods were identified as March–April-May 2019 (MAM-2019) and March–April-May 2020 (MAM-2020). As dried blood spots (DBS) have been proven to be a powerful sampling method to monitor PKUs metabolic control (in this study identified by mean of blood Phe values during analyzed time periods), they were reviewed and analyzed considering both monitoring frequencies and single obtained Phe value results [ 4 ]. Patients with less than 1 DBS performed per month were excluded due to possible related bias, as suggested by literature.…”
Section: Methodsmentioning
confidence: 99%
“…This would provide access to metabolic signatures coincident with self-reported psychological and physical state. Blood spot analysis reduces sensitivity so is currently more applicable to MS based methods [ 108 , 109 ].…”
Section: Discussionmentioning
confidence: 99%